Reconfiguring the burnt scar: a landscape architectural response to the Knysna fires of June 2017 - Brukman, Louise Kathleen (School of Architecture, Planning and Geomatics, 2018)
June 2017 will be remembered by South Africans for decades to come. A moment when Mother Nature showed her true power and the only options was to get out her path or watch in awe. Within 72hours 20 000 hectares of land and in excess of 800 homes were burnt in the Knysna region along the Garden Route. While fires are not uncommon in this area, this fire had all the conditions to make it 'The Perfect fire'. It was simply a matter of time for these conditions to align. This project begins with an understanding of conditions that caused the fire using the agent of time. Time, according to French philosopher, Henri Lefebvre, can be classified into three categories; Linear Time, Event Time and Cyclical Time. Through this process one is able to isolate the solvable from the unsolvable environmental conditions and thus an on going proposal for intervention can be proposed. The process of reconfiguring the burnt scar begins through the implementation of immediate solutions and long term planning. This project traverses a variety of scales due to the types of fuel load that contributed to the fire. The large areas of unmanaged fynbos, the pine plantations that border Knysna region and the havoc caused as it ripped through the urban settlements down to the domestic garden scale. At a regional scale the the reconfiguring of the burnt scar requires a management system that is responsible for immediate controlling of erosion post fire. As well as the monitoring and the implementation of controlled ecological burns of fynbos stands and the removal of alien invasive species. Furthermore, it is proposed that the reconfiguring of the burnt scar requires a restructuring of the commercial plantations and the establishment of critical fire breaks affecting the urban interface. The introduction of fire resistant non-native commercial trees mass scale present a landscape character and scenic value to the region that calls upon the ideals of the Picturesque. A significant contributing factor the fire was the fuel load within the suburban environment. This project proposes a vegetation palette that property owners could use in a variety of ways to form domestic scale fire break, that when in-conjunction with neighbours, a district break is established.